Altered cardiac reserve is a determinant of exercise intolerance in sickle cell anaemia patients. (21st August 2021) - Hammoudi, Nadjib; Ceccaldi, Alexandre; Haymann, Jean‐Philippe; Guedeney, Paul; Nicolas‐Jilwan, Fadila; Zeitouni, Michel; Montalescot, Gilles; Lionnet, François; Isnard, Richard; Hatem, Stéphane N.
Abstract: Background: The underlying mechanisms of exercise intolerance in sickle cell anaemia (SCA) patients are complex and not yet completely understood. While latent heart failure at rest could be unmasked upon exercise, most previous studies assessed cardiac function at rest. We aimed to investigate exercise cardiovascular reserve as a potential contributor to exercise intolerance in adult SCA patients. Methods: In this observational prospective study, we compared prospectively 60 SCA patients (median age 31 years, 60% women) to 20 matched controls. All subjects underwent symptom‐limited combined exercise echocardiography and oxygen uptake (VO2 ) measurements. Differences between arterial and venous oxygen content (C(a‐v)O2 ) were calculated. Cardiac reserve was defined as the absolute change in cardiac index (Ci) from baseline to peak exercise. Results: Compared to controls, SCA patients demonstrated severe exercise intolerance (median peakVO2, 34.3 vs. 19.7 ml/min/kg, respectively, p < .0001). SCA patients displayed heterogeneously increased Ci from rest to peak exercise (median +5.8, range 2.6 to 10.6 L/min/m²) which correlated with peakVO2 ( r = 0.71, p < .0001). In contrast, the C(a‐v)O2 exercise reserve was homogenously reduced and did not correlate with peakVO2 ( r = 0.18, p = .16). While haemoglobin level and C(a‐v)O2 were similar in SCA subgroups, SCA patients in the lower VO2 tertile had chronotropic incompetence and left ventricular diastolic dysfunction (left atrial peak longitudinal strain was reduced, and both E/e' ratio and left atrial volume index were increased) and were characterized by a reduced cardiac reserve, +5.0[4.2–5.5] compared to +6.7[5.5–7.8] L/min/m² for the rest of the patient cohort, p < .0001. Conclusions: Altered cardiac reserve due to chronotropic incompetence and left ventricular diastolic dysfunction seems to be an important determinant of exercise intolerance in adult SCA patients.